2007
DOI: 10.1177/1076029607308863
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recombinant Activated Factor VII to Arrest Uncontrolled Bleeding: A Case Series

Abstract: A retrospective analysis is described to assess the effects of using recombinant activated factor VII to control bleeding in a series of patients who had failed to respond to conventional hemostatic measures. In all, 18 patients (aged 16-65 years) with a range of conditions resulting in bleeding refractory to conventional methods of control were treated with recombinant activated factor VII (60-120 Amicrog/kg; 1-4 doses). The effects of recombinant activated factor VII on bleeding were noted together with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…After the report of successful use of rFVIIa in a patient suffering massive haemorrhage from a gunshot wound in 1999, rFVIIa has been used for various off‐label indications. Numerous case reports have been published as well as single institution case series on its use in critical non‐haemophilic bleeding, clinical observational studies in refractory bleeding and randomized clinical trials (RCTs) on bleeding in major cardiac surgery and in multitrauma . Although most studies have reported reduced bleeding or reduced transfusion requirement following administration of rFVIIa, three recent meta‐analyses on off‐label use have come to conflicting conclusions on mortality in massive haemorrhage, and concerns with increased arterial thromboembolic risk have been raised .…”
mentioning
confidence: 99%
“…After the report of successful use of rFVIIa in a patient suffering massive haemorrhage from a gunshot wound in 1999, rFVIIa has been used for various off‐label indications. Numerous case reports have been published as well as single institution case series on its use in critical non‐haemophilic bleeding, clinical observational studies in refractory bleeding and randomized clinical trials (RCTs) on bleeding in major cardiac surgery and in multitrauma . Although most studies have reported reduced bleeding or reduced transfusion requirement following administration of rFVIIa, three recent meta‐analyses on off‐label use have come to conflicting conclusions on mortality in massive haemorrhage, and concerns with increased arterial thromboembolic risk have been raised .…”
mentioning
confidence: 99%